Short-Term Adaptation Modulates Anaerobic Metabolic Flux to Succinate by Activating ExuT, a Novel D-Glucose Transporter in Escherichia coli - Kim, Hyun Ju; Jeong, Haeyoung; Lee, Sang Jun (Frontiers in Microbiology, 2020)
The sugar phosphotransferase system (PTS) is an essential energy-saving mechanism, particularly under anaerobic conditions. Since the PTS consumes equimolar phosphoenolpyruvate to phosphorylate each molecule of internalized glucose in the process of pyruvate generation, its absence can adversely affect the mixed acid fermentation profile and cell growth under anaerobic conditions. In this study, we report that the ptsG mutant cells of E. coli K-12 strain exhibited inefficient glucose utilization, produced a significant amount of succinate, and exhibited a low growth rate. However, cells adapted soon after and started to grow rapidly in the same batch culture. As a result, the adapted ptsG cells showed the same mixed acid fermentation profiles as the wild-type cells, which was attributed to the mutation of the mlc gene, a repressor of the D-mannose PTS, another transporter for D-glucose. Similar adaptations were observed in the cells with ptsG manX and the cells with ptsI that resulted in the production of a substantial amount of succinate and fast growth rate. The genome sequencing showed the presence of null mutations in the exuR gene, which encodes a modulator of exuT-encoded non-PTS sugar transporter, in adapted ptsGmanX and ptsI strains. Results from the RT-qPCR analysis and genetic test confirmed that the enhanced expression of ExuT, a non-PTS sugar transporter, was responsible for the uptake of D-glucose, increased succinate production, and fast growth of adapted cells. In conclusion, our study showed that the regulatory network of sugar transporters can be modulated by short-term adaptation and that downstream metabolic flux could be significantly determined by the choice of sugar transporters.